Perbandingan Efektivitas Ekstrak Daunn Kirinyuh (Chromolaena odorata) dan Povidone Iodine 10% Terhadap Angiogenesis Pada Luka Insisi Kulit Tikus Putih (Sprague dawley) - Panjaitan, Yolanda Indah Wirijayanti; Telussa, Arley Sadra; Sihotang, Jojor Sadra (Universitas Nusa Cendana, 2023)
Abstract Background: Wound is an injury or damage in the body tissue. The use of herb as traditional medicine for the treatment of wound was still commonly found. The siam weed leaf (Chromolaena odorata) is one of the herbs found in Indonesia which was still used as a traditional medicine for wound recovery. Siam weed leaf (Chromolaena odorata) has an effect in wound recovery and may increase angiogenesis. Povidone iodine 10% was currently the standard treatment for wound and has an antiseptic effect. Method: This is an experimental study. The mice was divided into 4 groups which were control group (P1) which was treated with Povidone iodine 10%, treatment group I (P2) which was treated with siam weed leaf (Chromolaena odorata) extract 10%, treatment group II (P3) which was treated with siam weed leaf (Chromolaena odorata) extract 15% and treatment group III (P4) which was treated with siam weed leaf (Chromolaena odorata) extract 20%. Angiogenesis was examined under microscope for angiogenesis count. Data was analyzed using the Kruskall Wallis test. Result: The result of this study showed the p value of p=0.294 (>0.05). Conclusion: Siam weed (Chromolaena odorata) leaf extract and Povidone iodine did not show any significant difference in effectivity to the angiogenesis in incision wound in Sprague dawley white mice.